The effect of Filmed modeling on the anxious and cooperative behavior of 4-6 years old children during dental treatment: A randomized clinical trial study - Mehrsa Paryab; Zeinab Arab (Wolters Kluwer Medknow Publications, 2014)
Background: The aim of this study was to evaluate the effect of Filmed modeling in comparison with commonly used Tell-Show-Do technique (T.S.D) on the anxious and cooperative behavior of 4-6 years old children during dental practice. Materials and Methods: Forty six children aged 4-6 years were enrolled in this study and randomly allocated into two groups. Group I: At the first visit, the procedure of Tell-Show-Do, and at the second visit, the treatment procedures were performed by the dentist for the children. Group II: At the first visit, children watched a film consisting of the procedure of Tell-Show-Do performed on a child model. At the second visit, treatment procedures were performed. In both groups, during the treatment procedure, index of heart rate was measured and behaviors of children were recorded. The children's anxious and cooperative behaviors on the recordings were quantified according to Venham and Frankl rating scales, respectively. The data were compared between two groups using T-test method. All statistical references were made at 0.05. Results: There were no statistically significant differences in heart rate measures, clinical anxiety and cooperative behavior scores of children between the two groups (P = 0.6). Conclusion: Filmed modeling can be an efficient alternative method to Tell-Show-Do technique in pre-appointment preparation of the 4-6 years old children during dental treatment.